2021
DOI: 10.1002/pc.26374
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical and thermal characterization of laminar carbon/epoxy composites modified with magnesium oxide microparticles

Abstract: This paper investigates the effects of magnesium oxide (MgO) microparticles on the mechanical and thermal properties of laminated carbon fiber reinforced polymer composites. The polymer epoxy matrix was modified with 0% (pure), 2 wt%, and 4 wt% MgO fillers. Then the laminar composites were manufactured with the vacuum bag method. The energy absorption capacity and impact strength were determined from the Charpy impact tests, whereas the flexural characteristics were evaluated by conducting three-point bending … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…In [16], it was shown that the addition of TiO 2 significantly changes the properties of the mixture, and a detailed description of this interaction was given depending on the size of the modifier, while in [17], SiO 2 was used to modify the electro-optical properties of polymer-dispersed liquid crystals. Metal oxides are also used to improve thermal and mechanical properties in epoxy composites, including epoxy compounds with mesogenic units [18][19][20]. Additionally, titanium dioxide is known for its photocatalytic activity and protective properties against the degradative effects of weather conditions, especially UV radiation [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…In [16], it was shown that the addition of TiO 2 significantly changes the properties of the mixture, and a detailed description of this interaction was given depending on the size of the modifier, while in [17], SiO 2 was used to modify the electro-optical properties of polymer-dispersed liquid crystals. Metal oxides are also used to improve thermal and mechanical properties in epoxy composites, including epoxy compounds with mesogenic units [18][19][20]. Additionally, titanium dioxide is known for its photocatalytic activity and protective properties against the degradative effects of weather conditions, especially UV radiation [21][22][23].…”
Section: Introductionmentioning
confidence: 99%
“…Many researchers have used metal oxide nanoparticles as additives in polymers because of their excellent properties. [ 1–6 ] Fe 2 O 3 , ZnO, NiO, Al 2 O 3 , TiO 2 , and MgO effects the positive direction of the magnetic, ultraviolet light absorption, electrochemical properties, fracture toughness, modulus of elasticity, and dielectric properties, respectively. Polymer nanocomposites are used in many applications, such as energy systems, biomechanics, aviation, [ 7 ] civil construction, automotive, [ 8 ] anti‐corrosion coating, and high voltage fields.…”
Section: Introductionmentioning
confidence: 99%
“…Fiber-reinforced epoxy matrix composite materials are increasingly used in areas such as aerospace, automotive, marine, and so forth. [1][2][3][4][5] Various fiber reinforcements such as glass and carbon are selected in accordance with the usage areas. Carbon fiber reinforced polymer (CFRP) composites show better strength properties but are more expensive than glass fiber reinforced polymer (GFRP) composites.…”
Section: Introductionmentioning
confidence: 99%